A Fresh Approach in the Optimization of Government Processes using Algorithms: A Case Study of Retirement Procedure in Cameroon. Issue 1 (5th December 2017) - Etoundi, Roger Atsa; Alo'o, Ghislain Abessolo; Ndjodo, Marcel Fouda
Abstract: Many works have been carried out in the field of business process re‐engineering. Despite their abundance, there is still much to be done as not all the aspects have been taken into consideration. Most of the works are concentrated on the reduction of the number of tasks and do not take into consideration the reduction of resources needed to perform tasks. Among these resources are documents required for the processing of various tasks. Even when tasks reduction is concerned, there is no clear methodology that is proposed for task cancellation. Moreover, among business processes are administrative procedures, which are specific processes dealing with policy, legislation rules and regulation in the administration. The optimization of administrative procedures has become imperative in developing countries as these countries are working to improve the quality of services delivered to citizens. It is an important aspect to be considered in order to move ahead in their development. Procedures actually used in these countries have been developed just at the dawn of independences. Their effectiveness in terms of quality of service was not considered as these countries first wanted to deliver. Forty years after, the problem of the quality of service became crucial. Hence, these countries are seeking solutions to re‐engineer their legacy administrative procedures. This paper presents a methodology associated with an algorithm for the reduction of documents required from citizens, and activities that are performed in the delivery of services. The methodology is based on the correlation among tasks and among documents. This methodology is applied to the management of the human resource retirement process in the public service in Cameroon.